PENGARUH OPINI AUDIT DAN KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KINERJA PEMERINTAH KABUPATEN/KOTA DI INDONESIA - Kusuma, Priyan Mardya; Kurnasih, Lulus (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
Due to the increasing authority of local governments, a systematic monitoring and evaluation system is needed to measure performance achieved by a local government. From the financial side, the Local Government Financial Report (LKPD) shows the accountability of a local government. With the quality of financial statements and information in it, it is expected that the performance of local government can increase. The purpose of this research is to know the influence between audit opinion and the characteristics of local government represented by variable of level of local government wealth, level of dependency on central government, and regional expenditure on local government performance. Samples were conducted on 440 district / city governments in Indonesia in 2015. The data analysis technique used is multiple linear regression. Based on the test results found that the level of local wealth have a positive effect on the performance of local government. The level of dependence on the central government negatively affects the performance of local governments. While the variables of audit opinion and regional expenditure do not affect the performance of local government.